Maintenance procedure and practice (E-Aduan) / Afa Raysad Haririe Sahra - Afa Raysad Haririe, Sahra (2018)
This report is content all about the information about my case study through practical training under company Development & Facility Management Office or Bahagian Pembangunan dan Pengurusan Faciliti (BPPF) during the four months of practical training. The topic that I have choose to complete my practical training report is maintenance process inside the UiTM Campus.This report has a 5 chapter which included all information about the company, general information about case study, information about case study which is focus on specific topic that I have choose, and also problems and recommendation that have been analyzed. The first chapter in this report is detail of information of the company. In this chapter, all the general information about the background of the company and the organization that owned by company that I choose to undergo the practical training. It also contents about the scope of work about this company, objective, mission, vision, location, and also panel company which is involved with the company of BPPF. The second chapter give out information about the literature review based on my case study. All the general information and overview about the topic that I have choose is included in this chapter. It content about the definition, types and etc. The third chapter list out all the information about my case study that have get from my observation and learning with my real experience at the Maintenance Management that I have involved under company of BPPF content about the specific information that I get through practical training. Forth chapter is the problems and recommendation that I have analyze during the completion of the practical training report. It all about focusing and identifying the problem that occurs regarding all the chapter in report. Some of the problem might be minor and some of them could be major, sometimes the minor problem that occurs are not be taken any action. The last chapter in this report is the conclusion of the whole chapter which is the summary of every chapter in this report.